2007
DOI: 10.1007/s00192-007-0327-7
|View full text |Cite
|
Sign up to set email alerts
|

A safety and quality of life analysis of intravaginal slingplasty in female stress incontinence: a prospective, open label, multicenter, and observational study

Abstract: This prospective, open label, multicenter, and observational study was performed to determine the efficacy, safety, and the impact of this procedure on the current quality of life (QOL). One hundred three women underwent the intravaginal slingplasty (IVS) procedure. (74/83) cure rate. During follow-up period, one patient (1.2%) has presented with vaginal erosion of the sling material. The I-QOL showed significant improvement in total and three subscale scores at 12 months of follow-up period. This study demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(29 reference statements)
0
9
0
3
Order By: Relevance
“…In several studies of the MUS procedure, the I-QoL questionnaire has been used to assess the QoL of incontinent patients and changes in QoL after the procedure. Campeau et al reported an increment of 38.7 points in the I-QoL after the TVT procedure (from 57.8 to 96.5 points) [2], and Kim et al reported an increment of 32.9 points in the I-QoL after the IVS procedure (from 61.5 to 94.4 points) [3]. Also, Kocjancic et al reported an increment of 40 points in the I-QoL after the TOT procedure (50.6 to 90.6 points) [12].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies of the MUS procedure, the I-QoL questionnaire has been used to assess the QoL of incontinent patients and changes in QoL after the procedure. Campeau et al reported an increment of 38.7 points in the I-QoL after the TVT procedure (from 57.8 to 96.5 points) [2], and Kim et al reported an increment of 32.9 points in the I-QoL after the IVS procedure (from 61.5 to 94.4 points) [3]. Also, Kocjancic et al reported an increment of 40 points in the I-QoL after the TOT procedure (50.6 to 90.6 points) [12].…”
Section: Discussionmentioning
confidence: 99%
“…9,261 In addition, the qualifiers persistent or de novo 261 were often used. De novo OAB, indicating the occurrence of OAB after sling surgery, was reported in 0-48% of patients in various studies (REFS 17,18,20,26,39,(46)(47)(48)(50)(51)(52)(53)55,(57)(58)(59)61,62,66,67,70,(73)(74)(75)(76)(77)79,83,87,88,91,92,96,97,99,140,152,153,155,157,159,161,163,164,(166)(167)(168)(170)(171)…”
Section: Oab Symptomsmentioning
confidence: 98%
“…In patients with SMUS-related infections, removal of the complete mesh is particularly important. Of course, many more serious infectious complications are likely to arise from the 'minor' ones listed above, 113 [132][133][134]140,145,146,148,[151][152][153]156,158,162,163,167,168,171,173,[176][177][178][179][181][182][183][184], or bowel) perforation at the time of trocar passage has been reported to occur in 0-16% of sling surgery procedures (0-14% for RP sling implantation and 0-16% for TOT sling implantation). In most reports, the authors usually downplay any substantial implications of pelvic organ perforations.…”
Section: Reviews Infectionmentioning
confidence: 99%
“…In a randomized trial comparing tension-free vaginal tape and intravaginal slingplasty (IVS), 9% of women treated with IVS required removal of the tape for erosions [5]. Other studies describe the erosion rate after type III mesh for the treatment of female urinary incontinence from 1.2 to 17% [6,7]. Posterior slingplasty is a technique used for the treatment of apical prolapse [8].…”
Section: Introductionmentioning
confidence: 99%